Planar nanowire arrays formed by atomic-terrace low-angle shadowing - SHVETS, IGOR; USOV, VICTOR; MURPHY, SHANE; O COILEAIN, CORMAC LUKE (My University, 2008)
A relatively simple method for preparation of planar nanowire arrays on vicinal substrates by molecular beam epitaxy is presented. The atomic step-and-terrace morphology of vicinal substrates is used to produce a shadowing effect on a highly collimated molecular beam at an oblique incidence to the substrate. The collimation is achieved by placing the evaporation source at a large working distance (40?100?cm) from the substrate. The method?s capabilities have been demonstrated by preparation of arrays of Ag and Au nanowires on vicinal Si(111) and ?-Al2O3 (0001) substrates. Nanowires with a width of down to 10?15?nm and a thickness of 1.5?nm have been readily achieved.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; Nanowires